Skrining Fitokimia Senyawa Metabolit Sekunder Pada Ekstrak Bunga Telang Clitoria ternatea - Wita Oileri Tikirik; Arifah Arifah; Askur Askur; Nasrullah Nasrullah (Jurnal Teknologi Pangan dan Industri Perkebunan (LIPIDA), 2026)
The telang flower (Clitoria ternatea) is a medicinal plant with various pharmacological activities. The aim of this study is to identify the phytochemical profile of the ethanol extract of Telang flowers grown in Mamuju City, West Sulawesi, using a qualitative method. The extraction was carried out using the maceration method with a 70% ethanol solution (1:10, b/v ratio) at room temperature for 72 hours, resulting in a yield of 12.8%. Phytochemical screening was conducted using the standard color test method to detect alkaloids (Mayer's, Wagner's, and Dragendorff's reagents), flavonoids (Shinoda's test), terpenoids/steroids (Liebermann-Burchard's test), saponins (foam test), and tannins (FeCl₃). The results showed that the ethanol extract of the Mamuju telang flower tested positive for alkaloids (positive with Wagner's reagent), flavonoids (reddish-yellow), terpenoids (yellowish-red), saponins (stable foam), and tannins (blue-black). This research is expected to provide material for further research on the benefits and uses of telang flowers in Mamuju.